Snake Diversity in Human Landscapes: A Comprehensive Study of Snake Species in Kushinagar, Uttar Pradesh, India - Ojha, Aazad Prakash; Kumar, Khagendra; Imran; Mishra, Sushil (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
This comprehensive study documents the diversity of snake species within the human landscape of Kushinagar district, Uttar Pradesh, India. Carrying out extensive fieldwork using direct and indirect encounter methods revealed 18 snake species from six families, with the Indian Spectacled Cobra (Naja naja) being the dominant venomous species, along with Russell's viper (Vipera russellii) and the Indian Common Krait (Bungarus caeruleus). Biostatistical analysis showed that the Colubridae family was the most diverse group, comprising 61% of the recorded snake species. Species richness, abundance, and diversity indices were analysed, with the Shannon Diversity Index (H') and Simpson Diversity Index (D) indicating variations in species richness and evenness across different areas. The correlation matrix highlighted ecological interactions, such as predator-prey dynamics and habitat sharing, while non-parametric tests revealed significant differences in abundance among the study areas. The study emphasizes the importance of utilizing additional biostatistical strategies to examine non-normally distributed data and ensure robust conclusions. The findings contribute to understanding snake ecology and provide valuable insights for habitat management and biodiversity conservation planning in the Kushinagar region, which is crucial for protecting these enigmatic animals and their ecosystems.